Addressing Ethnic Disparities in Adolescent Smoking: Is Reducing Exposure to Smoking in the Home a Key?. Issue 4 (15th March 2018) - Ball, Jude; Sim, Dalice; Edwards, Richard
Abstract: Introduction: Smoking among New Zealand (NZ) adolescents has declined since 2000, but ethnic disparities remain pronounced. To inform prevention efforts, we investigated exposure to and relative importance of known predictors of adolescent smoking and how these have changed over time, for Māori (NZ's indigenous population) and adolescents overall. Methods: We used repeat cross-sectional data, 2003–2015, from a national survey of 14- to 15-year olds ( N = 20 443–31 696 per year). For the overall sample and for Māori and non-Māori, we calculated adjusted odds ratios (aORs) to assess the association between regular smoking and risk factors each year: one or more parents smoke, best friend smokes, older sibling(s) smoke, and past week exposure to smoking in the home. We calculated population attributable risk (PAR) for risk factors in 2003 and 2015. Results: Between 2003 and 2015, aORs for exposure to smoking in the home increased from 1.7 (95% CI 1.6% to 1.8%) to 2.6 (2.1% to 3.1%) overall and from 1.8 (1.6% to 2.1%) to 3.4 (2.5% to 4.5%) for Māori; aORs for "best friend smokes" also increased, while aORs for sibling smoking and parental smoking did not change meaningfully. PAR for exposure to smoking in the home increased from 17% to 31% overall and from 28% to 57% for Māori, while PARs for other risk factors decreased. Conclusions: Exposure to smoking in the home has become more strongly associated with adolescent smoking over time and is an increasingly important risk factor at the population level (independent of parental smoking), particularly for Māori. Implications: Our findings have implications for reducing smoking uptake and ethnic disparities in NZ, and potentially elsewhere, given the similarity in risk factors and trends for adolescent smoking internationally. Our findings suggest that reducing second-hand smoke exposure in homes will likely reduce uptake of smoking. Because Māori children are both more exposed and appear to be more strongly influenced by exposure to smoking in the home, interventions to reduce indoor smoking could have differentially positive effects for Māori. Greater research and policy attention to reducing smoking in homes is warranted.